Overview Michelin Star Reputation Restaurant in Hospitality Industry - Agung Gita Subakti (Binus Business Review, 2013)
For most chefs and Restaurateur, having his restaurant being awarded one or more stars in the famous Michelin Guide Rouge represents a major achievement, recognition of their work, and also important publicity generating increased notoriety. In this speciﬁc industry, experts play a decisive role, and reputation of restaurants and chefs are basically established according to their opinions. The aim of this paper is to overview some of the Restaurants achieving the Michelin Star Reputation and able to sustain it for years. Moreover, how these reputations are made and to understand better the development of gaining such a high reputation.